Effect of pH for Colloid Stability in Chemically Heterogeneous Soils - Gunawardhana, T.; Balakrishnan, B.; Deepagoda (University of Jaffna, 2022)
Until recently, natural soils were believed to constitute two mobile phases: soil moisture and soil air. However, research revealed later the presence of another mobile phase, which is now referred as the colloidal phase, with a strong potential to facilitate the transport of toxic contaminants and various nutrients to groundwater, leading to significant health concerns. Colloids, consisting of soil particles of nano and micrometer scale, are highly reactive in subsurface and sensitive to the physico-chemical properties of soil, including soil pH. This study investigated the effect of pH on colloid transport using soil samples collected from two agricultural lands in Medawachchiya and Horowpathana in North Central Province of Sri Lanka, which were recognized as high-CKDu endemic and low-CKDu endemic areas, respectively. Stability of the colloids extracted from the two soil was investigated by varying the pH as 3, 5, 6, 7, 8, 11 in room temperature. According to the results, enhance colloid stability at higher pH values was observed for both soil types. Furthermore, colloid turbidity change with time was numerically characterized and parameterized with an exponential parametric function. These findings could be used effectively on controlling groundwater contamination via colloid-facilitated transport in subsurface in contaminated soils.
Keywords: Colloids; Colloid stability; Colloid facilitated transport; pH; Groundwater